The Effectiveness Student Entrepreneurship Program in Realizing Entrepreneur STIKOM Indonesia - Ni Made Mila Rosa Desmayani (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2021)
ABSTRACT This study aims to determine the effectiveness of the student entrepreneurial program in realizing entrepreneurial students of STMIK STIKOM Indonesia. The type of data used is secondary data. The data collection technique used was direct observation into the field. Research using a qualitative approach is descriptive, making a systematic picture, according to the facts in the field, the nature of the relationship between the phenomena being investigated. Collecting data using observation (direct observation in the field), interviews with related parties, and documentation. The data analysis used interactive model data analysis. This study uses the theory of program evaluation concepts, collects information about the work of something, which is then used to determine the right alternative in making a decision. With indicators of achievement of program evaluation indicators: achievement with a predetermined plan, supporting and inhibiting factors for the program being carried out, guidance and evaluation on subsequent activities, as well as supported by the theory of program effectiveness, achieving goals correctly or choosing the right goals from a series of alternatives or choice of means and choose from several other options. Effectiveness can also be interpreted as measuring success in achieving predetermined goals. Indicators of achievement: whether PMW has helped students hone skills in the field of entrepreneurship, appropriate that PMW is carried out at STMIK STIKOM Indonesia, the influence of entrepreneurial developing young entrepreneurs. The research results of the student entrepreneurial program have not been running optimally, due to the shortcomings in this business assistance that the period is considered unsustainable. The skill factor and the limited number of jobs are often the important issues behind it. Keywords: PMW, Enterpreneur, Effectiveness